Evaluation of the Şerefiye (Zara-Sivas) Dam According to Water Quality Indexes - Kutlu, Banu; Mutlu, Ekrem (Kastamonu University, 2024)
With the aim of determining the water quality of Şerefiye Dam, Sivas province, the present study was carried out on the samples collected monthly from 3 stations between January 2014 and December 2014. In the analyses, which examined 25 variables, water quality was determined using the World Health Organization drinking water standards, water quality index (WQI), sodium absorption ratio (SAR), sodium percentage, permeability index (PI), magnesium index, irrigation index, and the Surface Water Quality Regulation (SWQR) of the Turkish Ministry of Forestry and Water Affairs. The mean value of water quality index in the dam was found to be 46.82 and the mean value of IWOI irrigation was found to be 3.90. The results obtained here showed that Şerefiye Dam was in the "very good" class in terms of water quality index and irrigation water quality. In addition, there was no oxygen deficiency due to excessive oxygen consumption during organic matter decomposition. The water quality parameters were much lower than the thresholds set in the SWQR, but according to the results of factor analysis (FA), the main variables responsible for the processes in the ecosystem were TSS, COD, SO3, SO4, EC, BOD, NO3, NH4, DO and Fe
Keywords: Hidrobiyoloji; Hydrobiology; Şerefiye (Zara-Sivas); yüzey suyu su kalitesi; su kalite indeksi.; Şerefiye (Zara-Sivas); Surface water Water quality; Water quality index; 13. Climate action; 14. Life underwater; 15. Life on land; 6. Clean water